Male Gaze in 10 Tips to be More Elegant Lady Video by Farah Quinn (A Critical Discourse Analysis by Sara Mills) - Yuli Rahmawati Dewi; Eri Kurniawan (Universitas Muhammadiyah Semarang, 2022)
Patriarchy and gender stereotype lately proven as problems that disadvantage both woman and man (Hasyim, 2021). As this facts reveal, the discourse about gender friendly living and empowerment are keep growing. Unfortunately, it doesn’t mean that all idea about gender friendly living and empowerment in media are free from the bias. This research is going to prove a case about it. The writer found male gaze idea in a discourse that seems like talking about woman empowerment. This is found in a video tittled “10 Tips untuk Menjadi Wanita yang Lebih Elegan” (10 Tips to be More Elegant Lady). This research uses Scrutinize and Write method. The writer use Critical Discourse Analysis Theory by Sara Mills. This theory has three steps of analysis. There are analysis in the stage of word, phrase and discourse. From the analysis, the writer found that male gaze detected in the stage of word analysis, phrase analysis, spesifically in the presupposition and it also found in the stage of discourse analysis. From the analysis, we can conclude that eventhough a tittle of a discourse might sounds like empowering a certain gender, we still have to be careful and be aware of the messages it contains. So, we will not adopt the wrong perception. The writer also hopes that it can be a guidance for those who wants to make a discourse related about gender friendly living or empowerment.